Towards site specific Greenhouse Gases (GHGs) emissions measurement: rice in Colombia - Ibarra Medina, Lina Marcela; Romero Sánchez, Miguel Antonio; Andrade, Robert Santiago; González, Carolina (2022)
The effects of climate change, due to the increase in the accumulation of GHGs in the atmosphere, is one of the issues that has gained importance worldwide in recent years, because of the current threat to agri-food systems and its contribution to increase climate uncertainty. Therefore, estimating GHGs emissions is a fundamental process for constructing national emissions inventories that allow the development of low-emission national development strategies and adequate mitigation measures for decision makers. However, there are difficulties around the limited capacity of entities to collect site-specific data or specific measurements of emission factors, making it difficult to assess its impact. . In this presentation we propose an alternative simplified measurement procedure for GHG emissions using rice producer’s management decisions from a representative sample and existing emission factors for Colombia. Procedures like this provide site-specific GHG emission measurements that rely on socio-economic and biological datasets to guide policy mechanisms to reduce GHG.